The Effects of Earnings Quality, Conservatism, and Real Earnings Management on the Company's Performance and Information Asymmetry as a Moderating Variable - Machdar, Nera Marinda; Manurung D.R.M., Adler Haymans; Murwaningsari, Etty (International Journal of Economics and Financial Issues, 2017)
This study investigates the role of information asymmetry as a moderating variable to strengthen or to weaken the effects of earnings quality, conservatism, and real earnings management on the company's performance. This study utilized data from Indonesia and Singapore for years 2004 - 2013. The results suggest that earnings quality positively affects the company's performance; however accounting conservatism does not affect the company's performance and real earnings management negatively affects the company's performance. Moreover, information asymmetry weakens the effects of earnings quality and conservatism on the company's performance but strengthens the effect of real earnings management on the company's performance. Keywords: earnings quality; conservatism; real earnings management; the company's performance; information asymmetry. JEL classification: G10, G30